Implausible dream : the world-class university and repurposing higher education - Mittelman, James H. (Princeton : : Princeton University Press, 2018)
"Why the paradigm of the world-class university is an implausible dream for most institutions of higher education Universities have become major actors on the global stage. Yet, as they strive to be "world-class," institutions of higher education are shifting away from their core missions of cultivating democratic citizenship, fostering critical thinking, and safeguarding academic freedom. In the contest to raise their national and global profiles, universities are embracing a new form of utilitarianism, one that favors market power over academic values. In this book, James Mittelman explains why the world-class university is an implausible dream for most institutions and proposes viable alternatives that can help universities thrive in today's competitive global environment. Mittelman traces how the scale, reach, and impact of higher-education institutions expanded exponentially in the post-World War II era, and how the market-led educational model became widespread. Drawing on his own groundbreaking fieldwork, he offers three case studies--the United States, which exemplifies market-oriented educational globalization; Finland, representative of the strong public sphere; and Uganda, a postcolonial country with a historically public but now increasingly private university system. Mittelman shows that the "world-class" paradigm is untenable for all but a small group of wealthy, research-intensive universities, primarily in the global North. Nevertheless, institutions without substantial material resources and in far different contexts continue to aspire to world-class stature. An urgent wake-up call, Implausible Dream argues that universities are repurposing at the peril of their high principles and recommends structural reforms that are more practical than the unrealistic worldwide measures of excellence prevalent today. "--
Includes bibliographical references and index.
Keywords: Education, Higher -- Aims and objectives; Education, Higher -- Economic aspects; Universities and colleges -- Ratings and rankings; Education and globalization; Education, Higher -- United States; Education, Higher -- Finland; Education, Higher -- Uganda; EDUCATION / Higher; EDUCATION / Philosophy & Social Aspects; EDUCATION / Multicultural Education; EDUCATION / Aims & Objectives